Human Coronaviruses SARS-CoV, MERS-CoV, and SARS-CoV-2 in Children - Aleebrahim-Dehkordi, Elahe (J Pediatr Nurs, 2021)
The novel coronavirus, known as 2019-nCoV or severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has caused an epidemic with high mortality and morbidity since December 2019, in Wuhan, China. The infection has now been transmitted to more than 210 countries worldwide and caused more than 200,000 deaths. Similar to other coronaviruses such as Severe Acute Respiratory Syndrome Coronavirus (SARS-CoV) and the Middle East Respiratory Syndrome Coronavirus (MERS-CoV), SARS-CoV-2 appears to less commonly affect pediatrics and to cause less severe disease along with fewer symptoms compared to adults. Available data suggest that the pediatric population is just as likely as adults to become infected with SARS-CoV-2. However, they may be asymptotic or have milder symptoms than adults; they can be potential carriers of the disease. This article reviews the present understanding of SARS-CoV-2 infection in the pediatric age group in comparison with MERS-CoV and SARS-CoV.